Physical capacities and combat performance characteristics of male and female Olympic boxers - Hausen, M.; Taylor, L.; Bachini, F.; Freire, R.; Pereira, G.; Itaborahy, A. (Research Quarterly for Exercise and Sport, 2024)
Purpose The study characterized the anthropometrical and cardiorespiratory profile, and the cardiorespiratory, bio-chemical and immunological responses to 3 × 3 min round (R) free-contact/combat boxing simulation, in elite Olympic Boxers (4 female and 10 male).